Implementation strategies for interventions to improve the management of chronic kidney disease (CKD) by primary care clinicians: protocol for a systematic review. Issue 8 (8th August 2019) - Kamath, Celia C; Dobler, Claudia C; Lampman, Michelle A; Erwin, Patricia J; Matulis, John; Elrashidi, Muhamad; McCoy, Rozalina Grubina; Alsawaz, Mouaz; Pajouhi, Atieh; Vasdev, Amrit; Shah, Nilay D; Murad, M Hassan; et al.
Abstract : Introduction: There is a considerable implementation gap in managing early stage chronic kidney disease (CKD) in primary care despite the high prevalence and risk for increased morbidity and mortality associated with CKD. This systematic review aims to synthesise the evidence of efficacy of implementation interventions aimed at primary care practitioners (PCPs) to improve CKD identification and management. We further aim to describe the interventions' behavioural change components. Methods and analysis: We will conduct a systematic review of studies from 2000 to October 2017 that evaluate implementation interventions targeting PCPs and which include at least one clinically meaningful CKD outcome. We will search several electronic data bases and conduct reference mining of related systematic reviews and publications. An interdisciplinary team will independently and in duplicate, screen publications, extract data and assess the risk of bias. Clinical outcomes will include all clinically meaningful medical management outcomes relevant to CKD management in primary care such as blood pressure, chronic heart disease and diabetes target achievements. Quantitative evidence synthesis will be performed, where possible. Planned subgroup analyses include by (1) study design, (2) length of follow-up, (3) type of intervention, (4) type of implementation strategy, (5) whether a behavioural or implementation theory was used to guide study, (6) baseline CKD severity, (7) patient minority status, (8) study location and (9) academic setting or not. Ethics and dissemination: Approval by research ethics board is not required since the review will only include published and publicly accessible data. Review findings will inform a future trial of an intervention to promote uptake of CKD diagnosis and treatment guidelines in our primary care setting and the development of complementary tools to support its successful adoption and implementation. We will publish our findings in a peer-reviewed journal and develop accessible summaries of the results. PROSPERO registration number: CRD42018102441.